2010
DOI: 10.1124/jpet.110.173245
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 2-[[4-Fluoro-3-(trifluoromethyl)phenyl]amino]-4-(4-pyridinyl)-5-thiazolemethanol (JNJ-1930942), a Novel Positive Allosteric Modulator of the α7 Nicotinic Acetylcholine Receptor

Abstract: The ␣ 7 nicotinic acetylcholine receptor (nAChR) is a potential therapeutic target for the treatment of cognitive deficits associated with schizophrenia, Alzheimer's disease, Parkinson's disease, and attention-deficit/hyperactivity disorder. Activation of ␣ 7 nAChRs improved sensory gating and cognitive function in animal models and in early clinical trials. Here we describe the novel highly selective is obtained mainly by affecting the receptor desensitization characteristics, leaving activation and deactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 38 publications
2
64
0
Order By: Relevance
“…In support of a mechanistic role for α7 * nAChRs in schizophrenia, studies on auditory gating (investigated using the P50 auditory-evoked response), in which deficits are known to be associated with schizophrenia, have been done. The systemic administration of the type II α7 nAChR PAMs (PNU-120596 or JNJ-1930942) improved auditory gating deficits caused by amphetamine or MK-801 in rodent models that reflect circuit level disturbances associated with schizophrenia [141143]. Furthermore several clinical trials support the use of α7 nAChR agonists to treat cognitive deficits in schizophrenia.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…In support of a mechanistic role for α7 * nAChRs in schizophrenia, studies on auditory gating (investigated using the P50 auditory-evoked response), in which deficits are known to be associated with schizophrenia, have been done. The systemic administration of the type II α7 nAChR PAMs (PNU-120596 or JNJ-1930942) improved auditory gating deficits caused by amphetamine or MK-801 in rodent models that reflect circuit level disturbances associated with schizophrenia [141143]. Furthermore several clinical trials support the use of α7 nAChR agonists to treat cognitive deficits in schizophrenia.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…Similarly, JNJ-1930942 (described as an intermediate type α7 PAM with characteristics falling between the profiles of Type I and Type II modulators) has beneficial effects on the auditory-evoked sensory inhibition deficits in DBA/2 mice [147]. Interestingly, Stevens and colleagues [146] recently reported that while PNU 120596 was efficacious in reversing the sensory gating deficits in DBA/2 mice, the modulator was inactive in C3H Chrna7 heterozygote mice which display greater decreases in hippocampal α7 nAChRs (50–60%) than DBA/2 mice (~30%) and therefore, more closely matches the α7 nAChR deficits (~50) found in post-mortem brains of schizophrenics.…”
Section: Nachr Positive Allosteric Modulators-role As Standalone Amentioning
confidence: 99%
“…Compared to agonists, there is much less data regarding the cognitive effects of α7 nAChR PAMs in animals, and no published clinical data. However, documented effects include improvements of pre-pulse inhibition and auditory gating as well as short- and long-term memory [21][25], resembling the behavioral effects of the agonists. Since PAMs do not activate the receptor per se , but modulate the effects of endogenous transmitters, they may enable more subtle regulation of α7 nAChR responses compared to agonists [2], but on the other hand, a lack of activation by the PAMs alone may hamper their effectiveness in patients with decreased levels of endogenous activation.…”
Section: Introductionmentioning
confidence: 98%